Kemampuan Peserta Didik dalam Mengapresiasi Sastra pada Film “Budi Pekerti” Karya Wregas Bhanuteja - Desnatalie, Ernesta Laura; Sulastriana, Elva; Mastuti, Dewi Leni (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to describe students' understanding in appreciating literary works in the form of films, particularly the film Budi Pekerti by Wregas Bhanuteja. The study uses a qualitative descriptive method with a structural approach. The research subjects are students in class VIII.1 at SMP Negeri 1 Parindu. Data collection techniques include observation, documentation study, and written tests in the form of essays. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing, and was supported by content analysis of the students' answers based on the intrinsic elements and moral values of the film. The results of the study show that students are generally able to understand the plot and content of the film well and identify moral values such as honesty, responsibility, empathy, and wisdom in social media. Students also demonstrated an ability to appreciate the literary elements in the film, although some were still at the descriptive stage and had not yet reached the stage of interpreting implied meanings. The obstacles encountered included technical aspects of film presentation and difficulty in understanding symbols and implicit messages. Thus, the film Budi Pekerti is considered relevant and effective for use as a medium for teaching literature and as a means of character building in Indonesian language learning at the junior high school level.